Ferroelectric-piezoelectric ceramic energy storage material and hybrid process preparation method and application thereof
By mixing the sol with polycrystalline powder to form micro-nano composite structural particles, the problems of high sintering temperature and low energy storage density of lead zirconate ceramic materials are solved, and the sintering temperature and the energy storage density are reduced.
Patent Information
- Application Number
- CN202510033909.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-08
AI Technical Summary
The sintering temperature of existing lead zirconate-based ferroelectric-piezoelectric ceramic energy storage materials is relatively high, which limits its application in multi-layer ceramic capacitors and has a low energy storage density.
By mixing the sol with the polycrystalline powder and heat-treated, micro-nano composite structural particles are formed, which improves the specific surface area and oxygen vacancy content, thereby reducing the sintering temperature and improving dielectric energy storage performance.
The sintering temperature of ceramic materials is reduced to below 1150°C, which improves the energy storage density, simplifies the process flow and reduces production costs.
Smart Images

Figure CN119874356A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ferroelectric-piezoelectric ceramic materials, and in particular to a ferroelectric-piezoelectric ceramic energy storage material and a hybrid process preparation method and application thereof. Background Art
[0002] With the development of electronic information technology, ceramic capacitors, as an important electronic component, play an irreplaceable role in the electronics industry. Dielectric energy storage is an important application direction of ceramic capacitors, which puts forward new requirements for the performance of dielectric ceramic materials. Lead zirconate-based ferroelectric-piezoelectric ceramic energy storage materials have the advantages of high power density, fast discharge rate and long service life, and are important candidate materials for pulse power electronic components. However, its application in electronic energy storage components is limited by low energy storage density and high sintering temperature. This is because the co-sintering of dielectric ceramic materials and internal electrodes in multilayer ceramic capacitors requires that the ceramic materials have a sufficiently low sintering temperature. Taking the 70 / 30 palladium silver electrode as an example, its annealing temperature is 1150°C, but the sintering temperature of lead zirconate-based energy storage ceramics is generally around 1300°C. Therefore, it is necessary to reduce the sintering temperature of lead zirconate-based ceramic materials.
[0003] At present, it is generally believed that adding glass is an effective means to reduce the sintering temperature. In the invention with patent application number CN202010798450.5, the sintering temperature of lead-barium-lanthanum-zirconium-tin ceramics doped with barium-boron-aluminum-silicon glass phase is reduced to 1050°C, and the energy storage density is increased to 6.3J / cm 3 In the invention of patent application No. 202211297267.2, by adding BaCO3-B2O3-SiO2-K2CO3 glass phase, Pb 0.95 La 0.02 Sr 0.02 (Zr 0.5 Sn 0.4 Ti 0.1 The sintering temperature of O3 ceramic material is reduced from 1300℃ to 960℃, but its energy storage density is only 3.2J / cm 3 In these inventions, the addition of glass is not very effective in improving the energy storage properties and even sacrifices the dielectric constant of the material.
[0004] Whether it is ferroelectric-piezoelectric ceramic energy storage materials or other functional ceramic materials, lowering the sintering temperature is beneficial to saving energy and reducing production costs. How to improve the performance of energy storage materials while lowering the sintering temperature is a technical problem that needs to be solved urgently. Summary of the invention
[0005] The purpose of the present invention is to provide a ferroelectric-piezoelectric ceramic energy storage material and a hybrid process preparation method and application thereof, which forms particles of a micro-nano composite structure by mixing and calcining polycrystalline powder and sol, thereby increasing the specific surface area and oxygen vacancy content, which is beneficial to reducing the sintering temperature of the ceramic material and improving the dielectric energy storage performance of the ceramic material.
[0006] To achieve the above objectives, the present invention provides a ferroelectric-piezoelectric ceramic energy storage material, comprising polycrystalline powder and sol mixed evenly and then subjected to heat treatment to form micro-nano composite structure particles, the micro-nano composite structure particles comprising polycrystalline powder and a PLZS nano-component layer distributed around the polycrystalline powder.
[0007] Preferably, the weight ratio of the sol to the polycrystalline powder is 1-3:5.
[0008] Preferably, the chemical formula of the PLZS nanocomposition layer is (Pb 0.97 La 0.02 )(Zr 0.6 Sn 0.4 )O3.
[0009] Preferably, the chemical formula of the polycrystalline powder is (Pb 0.94 La 0.04 )(Zr 0.51 Sn 0.47 Hf 0.01 Ti 0.01 )O3(PLZSHT).
[0010] The hybrid process preparation method of the ferroelectric-piezoelectric ceramic energy storage material comprises the following steps:
[0011] S1, preparing sol and polycrystalline powder respectively;
[0012] S2, mixing the sol with the polycrystalline powder, removing organic matter by heat treatment, and obtaining micro-nano composite structure particles;
[0013] S3, mixing the micro-nano composite structure particles with a solvent, a binder, a dispersant and a plasticizer to obtain a casting slurry; the solvent is a mixture of ethanol and trichloroethylene, the binder is polyvinyl butyral, the dispersant is triethyl phosphate, and the plasticizer is dibutyl phthalate; the ratio of the micro-nano composite structure particles to the solvent, the binder, the dispersant and the plasticizer is 20:20:2:0.4:0.8;
[0014] S4, degassing and casting the casting slurry to obtain a thick film;
[0015] S5, shearing, laminating and hot pressing the thick film to obtain a ceramic green body;
[0016] S6. Debinding and sintering the ceramic green body to obtain a ferroelectric-piezoelectric ceramic energy storage material sample.
[0017] Preferably, in S1, the method for preparing the sol comprises the following steps:
[0018] S111, weighing lead acetate, lanthanum acetate, zirconium n-propoxide and tin isopropoxide according to a stoichiometric ratio;
[0019] S112, lead acetate and lanthanum acetate are dissolved in acetic acid, heated to 110°C and stirred, and after cooling, it is recorded as cup A; zirconium n-propoxide and tin isopropoxide are dissolved in ethylene glycol methyl ether, mixed and stirred, and acetylacetone is introduced, and the molar ratio of acetylacetone to PLZS content in the sol is about 1.1:1. After the sample is stirred evenly, it is recorded as cup B;
[0020] S113. Introduce the solution in cup B into the solution in cup A, mix and stir evenly, add deionized water, acetic acid and ethylene glycol to the mixture in sequence to adjust the concentration, pH and viscosity, and make up the volume with acetic acid after stirring to obtain a clear sol; the concentration of the sol is 0.027g / ml-0.08g / ml, the pH is 3-5, and the viscosity is 7cP-9cP.
[0021] Preferably, in S1, the method for preparing polycrystalline powder comprises the following steps:
[0022] S121, mixing lead tetroxide, lanthanum trioxide, zirconium dioxide, tin dioxide, hafnium dioxide and titanium dioxide according to a stoichiometric ratio, and performing a first ball milling, wherein the first ball milling time is 20h-30h;
[0023] S122, drying the mixture obtained after the first ball milling, and pre-calcining the mixture at a temperature of 900° C. for a pre-calcining holding time of 3 h, and cooling the mixture to room temperature with the furnace to obtain a pre-calcined mixture;
[0024] S123, ball milling the pre-sintered mixture for a second time, the second ball milling time being 20h-30h; drying the mixture after the second ball milling to obtain polycrystalline powder.
[0025] Preferably, in S2, the heat treatment temperature is 600° C., the heat treatment holding time is 5 h-7 h, and the furnace is cooled to room temperature.
[0026] Preferably, in S6, the binder removal temperature is 600°C, the binder removal insulation time is 8 hours, and the furnace is cooled to room temperature; the sintering temperature is 1100°C-1130°C, the sintering insulation time is 3 hours, and the furnace is cooled to room temperature.
[0027] The ferroelectric-piezoelectric ceramic energy storage material prepared by the hybrid process preparation method of the ferroelectric-piezoelectric ceramic energy storage material is used in electronic functional materials and devices.
[0028] The advantages and positive effects of the ferroelectric-piezoelectric ceramic energy storage material and the hybrid process preparation method and application thereof described in the present invention are:
[0029] 1. The present invention obtains raw materials of micro-nano composite structure by mixing sol with polycrystalline powder and removing organic matter. The sol component effectively reduces the grain size after sintering and improves the breakdown strength. There is space charge polarization in the composite ceramic material, and the introduced orthogonal phase has a higher polarization strength, thereby improving the dielectric constant. The energy storage density of the ceramic material prepared by the hybrid process of the present invention is greatly improved, which is conducive to solving the problem of volume limitation of energy storage capacitors.
[0030] 2. The sintering temperature of the ferroelectric-piezoelectric ceramic energy storage material prepared by the hybrid process of the present invention is 1120°C, which is 180°C lower than the sintering temperature of the ceramic prepared without the composite sol, which is conducive to the low-temperature co-firing of the inner electrode and the ceramic material in the multilayer ceramic capacitor. The present invention reduces the sintering temperature of the ferroelectric-piezoelectric ceramic energy storage material to below the co-firing temperature of the Ag-Pd electrode of 1150°C, which has a very large application significance.
[0031] 3. The hybrid process described in the present invention is simple, easy to repeat, does not require the introduction of large equipment, is low in cost, and can be mass-produced.
[0032] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 It is a flow chart of the hybrid process preparation method of the ferroelectric-piezoelectric ceramic energy storage material of the present invention;
[0034] Figure 2 XRD diagrams of the ferroelectric-piezoelectric ceramic energy storage material samples obtained in Examples 1-3 of the present invention and the ceramic material obtained in Comparative Example 1;
[0035] Figure 3 The SEM images of the ferroelectric-piezoelectric ceramic energy storage material samples obtained in Examples 1-3 of the present invention and the ceramic material obtained in Comparative Example 1; (a) is the SEM image of the ceramic material image of Comparative Example 1; (b) is the SEM image of the ferroelectric-piezoelectric ceramic energy storage material sample of Example 1; (c) is the SEM image of the ferroelectric-piezoelectric ceramic energy storage material sample of Example 2; (d) is the SEM image of the ferroelectric-piezoelectric ceramic energy storage material sample of Example 3;
[0036] Figure 4 The dielectric constant-temperature curves of the ferroelectric-piezoelectric ceramic energy storage material samples obtained in Examples 1-3 of the present invention and the ceramic material obtained in Comparative Example 1;
[0037] Figure 5Room temperature hysteresis loop diagrams of the ferroelectric-piezoelectric ceramic energy storage material samples obtained in Examples 1-3 of the present invention and the ceramic material obtained in Comparative Example 1;
[0038] Figure 6 The energy storage performance results of the ferroelectric-piezoelectric ceramic energy storage material samples obtained in Examples 1-3 of the present invention and the ceramic material obtained in Comparative Example 1;
[0039] Figure 7 TEM of the micro-nano composite structure particles obtained in Example 2 of the present invention Figure 1 ;
[0040] Figure 8 TEM of the micro-nano composite structure particles obtained in Example 2 of the present invention Figure 2 ;
[0041] Fig. 9 This is the underdamped discharge condition of the ferroelectric-piezoelectric ceramic energy storage material sample obtained in Example 2 of the present invention. DETAILED DESCRIPTION
[0042] In this application, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by technicians in the technical field of this application. In the event of any inconsistency, the meaning described in this specification or the meaning derived from the contents recorded in this specification shall prevail. In addition, the terms used herein are only for the purpose of describing the embodiments of the present application and are not intended to limit the present application. In order to accurately describe the technical content in this application and to accurately understand the present invention, the following explanations or definitions are given to the terms used in this specification before describing the specific embodiments:
[0043] The embodiments of the present invention are described in detail below in conjunction with the accompanying drawings.
[0044] A ferroelectric-piezoelectric ceramic energy storage material comprises uniformly mixed polycrystalline powder and sol, which are formed into micro-nano composite structure particles after heat treatment. The micro-nano composite structure particles include polycrystalline powder and a PLZS nano-component layer distributed around the polycrystalline powder.
[0045] The weight ratio of sol to polycrystalline powder is 1-3:5.
[0046] The general chemical formula of the PLZS nanocomposition layer is (Pb 0.97 La 0.02 )(Zr 0.6 Sn 0.4 )O3. The PLZS nanocomposition layer is an orthorhombic phase material with higher polarization intensity.
[0047] The general chemical formula of polycrystalline powder is (Pb 0.94 La0.04 )(Zr 0.51 Sn 0.47 Hf 0.01 Ti 0.01 )O3. Polycrystalline powder is a tetragonal phase material with the characteristics of phase change dispersion, but its polarization strength and breakdown strength are low, and the sintering temperature is higher than 1300℃.
[0048] like Figure 1 The hybrid process preparation method of the above ferroelectric-piezoelectric ceramic energy storage material comprises the following steps:
[0049] S1. Prepare sol and polycrystalline powder respectively.
[0050] The preparation method of the sol comprises the following steps:
[0051] S111. Weigh lead acetate, lanthanum acetate, zirconium n-propoxide and tin isopropoxide according to a stoichiometric ratio.
[0052] S112. Dissolve lead acetate and lanthanum acetate in acetic acid, heat to 110°C and stir, and record it as cup A after cooling. Dissolve zirconium n-propoxide and tin isopropoxide in ethylene glycol methyl ether, mix and stir, introduce chelating agent acetylacetone, and stir and mix evenly, record it as cup B. Acetylacetone can react with metal ions such as zirconium ions to form a chelate reaction. By coordinating with zirconium ions, the hydrolysis rate of metal ions can be controlled, making the hydrolysis process more uniform and slow, avoiding the rapid hydrolysis of metal ions to produce precipitation, and helping to form a stable sol system. Acetylacetone can also improve the stability of the sol, reduce particle agglomeration, and make the prepared sol have better dispersibility.
[0053] S113. Introduce the solution in cup B into the solution in cup A, mix and stir evenly, add deionized water, acetic acid and ethylene glycol to the mixed solution in sequence to adjust the concentration, pH and viscosity, and after stirring, make up the volume with acetic acid to obtain a clear sol.
[0054] The concentration of the sol is 0.027g / ml-0.08g / ml, the pH value is 3-5, and the viscosity is 7cP-9cP.
[0055] The method for preparing polycrystalline powder comprises the following steps:
[0056] S121, lead tetroxide, lanthanum trioxide, zirconium dioxide, tin dioxide, hafnium dioxide and titanium dioxide are mixed according to a stoichiometric ratio and subjected to a first ball milling. The medium of the first ball milling is alcohol, the grinding balls are zirconium oxide, and the first ball milling time is 20h-30h.
[0057] S122, drying the mixture obtained after the first ball milling, and pre-calcining the mixture at a temperature of 900° C. The pre-calcining holding time is 3 hours, and the mixture is cooled to room temperature in the furnace to obtain a pre-calcined mixture.
[0058] S123, the pre-sintered mixture is subjected to a second ball milling, the medium of the second ball milling is alcohol, the grinding balls are zirconium oxide, the second ball milling time is 20h-30h, and the mixture is passed through a 150-mesh sieve. The mixture after the second ball milling is dried to obtain micron-grade polycrystalline powder.
[0059] S2, mixing the sol and the polycrystalline powder and ball milling for 24 hours, drying and obtaining a mixture, and heat treating the mixture to remove organic matter and obtain micro-nano composite structure particles.
[0060] The heat treatment temperature is 600℃. The heat treatment holding time is 6h. Cool down to room temperature with the furnace.
[0061] Lead zirconate-based particles are dispersed in an organic sol, and organic matter is burned off at a relatively low temperature of 600° C. to prevent the lead zirconate-based particles in the sol from growing.
[0062] S3. Preliminary crushing of the micro-nano composite structure particles to improve the uniformity of the mixing of the micro-nano composite structure particles. The micro-nano composite structure particles are mixed with ethanol, trichloroethylene and triethyl phosphate and roll-milled for 4 hours to obtain a uniform and stable slurry. Then polyvinyl butyral and dibutyl phthalate are added to the slurry and roll-milled for 2 hours to obtain a casting slurry. The weight ratio of the micro-nano composite structure particles to the solvent, adhesive, dispersant and plasticizer is 20:20:2:0.4:0.8
[0063] S4, vacuum the casting slurry to remove bubbles, and scrape out the green sheet with a scraper to obtain a thick film.
[0064] S5. After the thick film is sheared, laminated and hot-pressed, a ceramic green body is obtained.
[0065] S6. Debinding and sintering the ceramic green body to obtain a ferroelectric-piezoelectric ceramic energy storage material sample.
[0066] The debinding temperature is 600℃. The debinding holding time is 8h. The furnace is cooled to room temperature. The debinding process removes organic matter from the ceramic green body.
[0067] The sintering temperature is 1100°C-1130°C, the sintering holding time is 3h, and the furnace is cooled to room temperature.
[0068] Example 1
[0069] The chemical formulas of sol and polycrystalline powder are (Pb 0.97 La 0.02 )(Zr 0.6 Sn 0.4 )O3 and (Pb 0.94 La 0.04 )(Zr 0.51 Sn0.47 Hf 0.01 Ti 0.01 )O3. The concentration of the sol is 0.027g / ml, and the volume is 150ml. The weight of the polycrystalline powder is 20g. The weight ratio of the sol to the polycrystalline powder is 1:5.
[0070] The hybrid process preparation method of ferroelectric-piezoelectric ceramic energy storage material comprises the following steps:
[0071] S1. Pb3O4, La2O3, ZrO2, SnO2, HfO2, and TiO2 powders are weighed according to the stoichiometric ratio, mixed by wet ball milling, dried after ball milling for 24 hours, sintered at 900°C, and kept warm for 2 hours to obtain a pre-fired mixture. The pre-fired mixture is ball milled for the second time, and dried after ball milling for 24 hours to obtain polycrystalline powder.
[0072] Lead acetate, lanthanum acetate, zirconium n-propoxide and tin isopropoxide were mixed in stoichiometric ratios, lead acetate and lanthanum acetate were dissolved in acetic acid, heated to 110°C, mixed and stirred for 2 hours, and then cooled to be recorded as cup A. Zirconium n-propoxide and tin isopropoxide were mixed and stirred in ethylene glycol methyl ether for 2 hours, and then acetylacetone was introduced. The molar ratio of acetylacetone to lead zirconate-based sol was 1.1:1, and then mixed and recorded as cup B. The solution in cup B was introduced into the solution in cup A and mixed and stirred, and deionized water, acetic acid and ethylene glycol were introduced in sequence to adjust the concentration, pH and viscosity. After stirring for 2 hours, the volume was fixed with acetic acid to obtain a clear sol of 0.027 g / ml, pH 4, and viscosity 8 cP.
[0073] S2, 20g of polycrystalline powder and 150ml of sol were mixed and ball-milled for 24h. The mixture was dried and kept at 600°C for 6h to remove organic matter by heat treatment, thereby obtaining micro-nano composite structure particles.
[0074] S3. The micro-nano composite structure particles are mixed with ethanol, trichloroethylene and tributyl phosphate and roll-milled for 4 hours to obtain a uniform and stable slurry. Then, polyvinyl butyral, dibutyl phthalate and polyethylene glycol are added to the slurry and roll-milled for 2 hours to obtain a casting slurry.
[0075] S4. Vacuum the slurry to remove bubbles and scrape out the blank with a scraper.
[0076] S5. After the green sheet is pressed into shape, the temperature is raised to 600 min and heat-treated for 8 hours to remove organic matter to obtain a ceramic green sheet.
[0077] S6. Sinter the ceramic green body at 1120° C. for 3 h to obtain a ferroelectric-piezoelectric ceramic energy storage material sample.
[0078] Example 2
[0079] The chemical formulas of sol and polycrystalline powder are (Pb 0.97La 0.02 )(Zr 0.6 Sn 0.4 )O3 and (Pb 0.94 La 0.04 )(Zr 0.51 Sn 0.47 Hf 0.01 Ti 0.01 )O3. The sol concentration is 0.053g / ml, the volume is 150ml. The weight of the polycrystalline powder is 20g. The weight ratio of the sol to the polycrystalline powder is 2:5.
[0080] The hybrid process preparation method of ferroelectric-piezoelectric ceramic energy storage material is the same as that in Example 1.
[0081] Example 3
[0082] The chemical formulas of sol and polycrystalline powder are (Pb 0.97 La 0.02 )(Zr 0.6 Sn 0.4 )O3 and (Pb 0.94 La 0.04 )(Zr 0.51 Sn 0.47 Hf 0.01 Ti 0.01 )O3. The sol concentration is 0.08g / ml, the volume is 150ml. The weight of the polycrystalline powder is 20g. The weight ratio of the sol to the polycrystalline powder is 3:5.
[0083] The hybrid process preparation method of ferroelectric-piezoelectric ceramic energy storage material is the same as that in Example 1.
[0084] Comparative Example 1
[0085] In Comparative Example 1, the sol mixing amount is 0, and only the (Pb 0.94 La 0.04 )(Zr 0.51 Sn 0.47 Hf 0.01 Ti 0.01 )O3 polycrystalline powder is made into ceramics.
[0086] The hybrid process preparation method of ferroelectric-piezoelectric ceramic energy storage material comprises the following steps:
[0087] The powders of Pb3O4, La2O3, ZrO2, SnO2, HfO2, and TiO2 are weighed according to the stoichiometric ratio, mixed by wet ball milling, dried after ball milling for 24 hours, sintered at 900°C, and kept warm for 2 hours to obtain a pre-burned mixture. The pre-burned mixture is ball milled for the second time, ball milled for 24 hours, and dried to obtain polycrystalline powder.
[0088] The polycrystalline powder was mixed with ethanol, trichloroethylene and tributyl phosphate and roll-milled for 4 hours to obtain a uniform and stable slurry. Then, polyvinyl butyral, dibutyl phthalate and polyethylene glycol were added to the slurry and roll-milled for 2 hours to obtain a casting slurry.
[0089] The slurry was vacuumed for 5 minutes to remove bubbles, and the green sheet was scraped out with a scraper.
[0090] After the green sheet is pressed into shape, the temperature is raised to 600 min and heat-treated for 8 hours to remove organic matter to obtain a ceramic green sheet.
[0091] The ceramic material was obtained by sintering the ceramic green body at 1300°C for 3 hours.
[0092] XRD analysis was performed on the ferroelectric-piezoelectric ceramic energy storage material samples obtained in Examples 1-3 and the ceramic material obtained in Comparative Example 1. The results are as follows: Figure 2 As shown. The ceramic material in Comparative Example 1 is a tetragonal perovskite phase. The ferroelectric-piezoelectric ceramic energy storage material in Example 1 is a pure perovskite phase, mainly a tetragonal phase, but contains a small amount of orthorhombic phase compared to Comparative Example 1. The ferroelectric-piezoelectric ceramic energy storage material in Example 2 is a pure perovskite phase, mainly a tetragonal phase, but the orthorhombic phase content of the energy storage material is increased compared to Example 1. The ferroelectric-piezoelectric ceramic energy storage material in Example 3 is a pure perovskite phase, mainly a tetragonal phase, and the orthorhombic phase content is the highest.
[0093] The ferroelectric-piezoelectric ceramic energy storage material samples obtained in Examples 1-3 and the ceramic material obtained in Comparative Example 1 were subjected to SEM analysis. The results are as follows: Figure 3 As shown. The grain size of the ceramic material in Comparative Example 1 is relatively large, with a small number of holes. The grain size of the ferroelectric-piezoelectric ceramic energy storage material in Example 1 is smaller than that in Comparative Example 1, and there are no obvious holes. The grain size of the ferroelectric-piezoelectric ceramic energy storage material in Example 2 is even smaller, and there are no obvious holes. The grain size of the ferroelectric-piezoelectric ceramic energy storage material in Example 3 is the smallest, and there are a small number of holes.
[0094] Figure 4The dielectric constant-temperature curves of the ferroelectric-piezoelectric ceramic energy storage material samples obtained in Examples 1-3 of the present invention and the ceramic material obtained in Comparative Example 1. The results show that the dielectric constant of the ceramic material in Comparative Example 1 is lower than that in Examples 1-3, and it exhibits a wider dielectric peak in the temperature range of 150°C-360°C, which is a typical phase change dispersion behavior. The dielectric constant of the ferroelectric-piezoelectric ceramic energy storage material in Example 1 is higher than that of the ceramic material in Comparative Example 1, and it exhibits a wider dielectric peak in the temperature range of 150°C-360°C, but the phase change dispersion is lower than that in Comparative Example 1. The dielectric constant of the ferroelectric-piezoelectric ceramic energy storage material in Example 2 is higher than that of the ferroelectric-piezoelectric ceramic energy storage material in Example 1, and it exhibits a wider dielectric peak in the temperature range of 150°C-360°C, but the phase change dispersion is lower than that in Example 1. The ferroelectric-piezoelectric ceramic energy storage material in Example 3 has the highest dielectric constant, exhibits a relatively broad dielectric peak in the temperature range of 150° C.-360° C., and has the lowest phase change dispersivity.
[0095] Figure 5 The room temperature hysteresis loop diagrams of the ferroelectric-piezoelectric ceramic energy storage material samples obtained in Examples 1-3 of the present invention and the ceramic material obtained in Comparative Example 1, Figure 6 The energy storage performance results of the ferroelectric-piezoelectric ceramic energy storage material samples obtained in Examples 1-3 of the present invention and the ceramic material obtained in Comparative Example 1 are shown in Figure 1. The breakdown field strength of the ceramic material in Comparative Example 1 is 517 kV / cm, and the maximum polarization strength is 36.4 μC / cm 2 , effective energy storage density is 9.5J / cm 3 The energy storage efficiency is 95.3%. The breakdown field strength of the ferroelectric-piezoelectric ceramic energy storage material in Example 1 is 664 kV / cm, and the maximum polarization strength is 41.7 μC / cm 2 , the effective energy storage density is 12.1J / cm 3 The energy storage efficiency is 94.1%. The breakdown field strength of the ferroelectric-piezoelectric ceramic energy storage material in Example 2 is 664 kV / cm, and the maximum polarization strength is 43.6 μC / cm 2 , the effective energy storage density is 12.4J / cm 3 The energy storage efficiency is 92.4%. The breakdown field strength of the ferroelectric-piezoelectric ceramic energy storage material in Example 3 is 595 kV / cm, and the maximum polarization strength is 43.0 μC / cm 2 , the effective energy storage density is 6.04J / cm 3 , the energy storage efficiency is 86.7%.
[0096] Figure 7 TEM of the micro-nano composite structure particles obtained in Example 2 of the present invention Figure 1 , Figure 8 TEM of the micro-nano composite structure particles obtained in Example 2 of the present invention Figure 2 The micro-nano composite structure particles present a state of two distinct composite parts, one of which is a crystalline state with neatly arranged lattice fringes, and the other is an amorphous mixed microcrystalline state. The sol component is included in the outside of the polycrystalline powder. Fig. 9 This is the underdamped discharge of the ferroelectric-piezoelectric ceramic energy storage material sample obtained in Example 2 of the present invention. When the electric field strength is 311 kV / cm, its power density reaches 289 MW / cm 3 , current density is 1860A / cm 2 , the discharge period is 59ns.
[0097] Therefore, by adopting the ferroelectric-piezoelectric ceramic energy storage material and its hybrid process preparation method and application described in the present invention, particles of micro-nano composite structure are formed by mixing and calcining polycrystalline powder and sol, which increases the specific surface area and oxygen vacancy content, helps to reduce the sintering temperature of the ceramic material and improve the dielectric energy storage performance of the ceramic material.
[0098] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A ferroelectric-piezoelectric ceramic energy storage material, characterized in that: The method comprises the steps of uniformly mixing polycrystalline powder and sol and then subjecting the mixture to heat treatment to form micro-nano composite structure particles, wherein the micro-nano composite structure particles comprise polycrystalline powder and a PLZS nano-component layer distributed around the polycrystalline powder.
2. The ferroelectric-piezoelectric ceramic energy storage material according to claim 1, characterized in that: The weight ratio of the sol to the polycrystalline powder is 1-3:
5.
3. The ferroelectric-piezoelectric ceramic energy storage material according to claim 2, characterized in that: The chemical formula of the PLZS nanocomposition layer is (Pb 0.97 La 0.02 )(Zr 0.6 Sn 0.4 )O3.
4. The ferroelectric-piezoelectric ceramic energy storage material according to claim 2, characterized in that: The chemical formula of the polycrystalline powder is (Pb 0.94 La 0.04 )(Zr 0.51 Sn 0.47 Hf 0.01 Ti 0.01 )O3.
5. A hybrid process preparation method for a ferroelectric-piezoelectric ceramic energy storage material as claimed in any one of claims 3 or 4, characterized in that: The following steps are involved: S1, preparing sol and polycrystalline powder respectively; S2, mixing the sol with the polycrystalline powder, removing organic matter by heat treatment, and obtaining micro-nano composite structure particles; S3, mixing the micro-nano composite structure particles with a solvent, a binder, a dispersant and a plasticizer to obtain a casting slurry; the solvent is a mixture of ethanol and trichloroethylene, the binder is polyvinyl butyral, the dispersant is triethyl phosphate, and the plasticizer is dibutyl phthalate; the mass ratio of the micro-nano composite structure particles to the solvent, the binder, the dispersant and the plasticizer is 20:20:2:0.4:0.8; S4, degassing and casting the casting slurry to obtain a thick film; S5, shearing, laminating and hot pressing the thick film to obtain a ceramic green body; S6. Debinding and sintering the ceramic green body to obtain a ferroelectric-piezoelectric ceramic energy storage material sample.
6. The hybrid process preparation method of a ferroelectric-piezoelectric ceramic energy storage material according to claim 5, characterized in that: In S1, the preparation method of the sol comprises the following steps: S111, weighing lead acetate, lanthanum acetate, zirconium n-propoxide and tin isopropoxide according to a stoichiometric ratio; S112, lead acetate and lanthanum acetate are dissolved in acetic acid, heated to 110°C and stirred, and after cooling, it is recorded as cup A; zirconium n-propoxide and tin isopropoxide are dissolved in ethylene glycol methyl ether, mixed and stirred, and acetylacetone is introduced, the molar ratio of acetylacetone to PLZS content in the sol is 1.1:1, and after stirring and mixing evenly, it is recorded as cup B; S113. Introduce the solution in cup B into the solution in cup A, mix and stir evenly, add deionized water, acetic acid and ethylene glycol to the mixture in sequence to adjust the concentration, pH and viscosity, and make up the volume with acetic acid after stirring to obtain a clear sol; the concentration of the sol is 0.027g / ml-0.08g / ml, the pH is 3-5, and the viscosity is 7cP-9cP.
7. The hybrid process preparation method of a ferroelectric-piezoelectric ceramic energy storage material according to claim 5, characterized in that: In S1, the method for preparing polycrystalline powder comprises the following steps: S121, mixing lead tetroxide, lanthanum trioxide, zirconium dioxide, tin dioxide, hafnium dioxide and titanium dioxide according to a stoichiometric ratio, and performing a first ball milling, wherein the first ball milling time is 20h-30h; S122, drying the mixture obtained after the first ball milling, and pre-burning, the pre-burning temperature is 900° C., the pre-burning holding time is 1h-3h, and the mixture is cooled to room temperature with the furnace to obtain a pre-burned mixture; S123, ball milling the pre-sintered mixture for a second time, the second ball milling time being 20h-30h; drying the mixture after the second ball milling to obtain polycrystalline powder.
8. The hybrid process preparation method of a ferroelectric-piezoelectric ceramic energy storage material according to claim 5, characterized in that: In S2, the heat treatment temperature is 600° C., the heat treatment holding time is 5 h-7 h, and the furnace is cooled to room temperature.
9. The hybrid process preparation method of a ferroelectric-piezoelectric ceramic energy storage material according to claim 5, characterized in that: In S6, the binder removal temperature is 600°C, the binder removal insulation time is 7h-10h, and the furnace is cooled to room temperature; the sintering temperature is 1100°C-1130°C, the sintering insulation time is 3h, and the furnace is cooled to room temperature.
10. Application of the ferroelectric-piezoelectric ceramic energy storage material prepared by the hybrid process preparation method of the ferroelectric-piezoelectric ceramic energy storage material according to any one of claims 6 to 9 in electronic functional materials and devices.
Citation Information
Patent Citations
Low-sintering anti-ferroelectric ceramic material for high-energy-storage-density capacitors and preparation method thereof
CN111995391A
Antiferroelectric material co-fired with base metal inner electrode and preparation method thereof
CN115947598B
High-energy-storage-density low-titanium lead zirconate-based antiferroelectric ceramic and preparation method thereof
CN111548154A
High-energy-storage lead zirconate-based antiferroelectric multilayer ceramic capacitor and preparation method thereof
CN111574198A
Piezoelectric ceramic, method for its production and electro-ceramic component comprising the piezoelectric ceramic
DE102016107405A1
Cited By
Ferroelectric-piezoelectric ceramic energy storage materials, hybrid process preparation methods, and use thereof
US12620529B1